Developing Cultural Competence in Rural Nursing - Lindsay L. Morgan; Sally Reel (Online Journal of Rural Nursing and Health Care, 2012)
Preconceptions of rural lifestyle and culture can color the perspective of future health care providers. To encourage Advanced Practice Nurse (ANP) students to think beyond the mythology about a rural place different than where they practice, two nurse educators and universities teamed up to develop a unique curriculum in which students immersed themselves in a new rural experience. In this innovative curriculum design, students visited a rural Appalachian coal-mining community in an immersion experience to conduct a community assessment and worked with local health care providers in community health education projects in collaboration with a nurse educator and ANP who provides health care to the community through a primary care clinic. The students discovered for themselves the distinctions of rural life in rural West Virginia. This project led to experiential learning and heightened attainment of cultural competence on the part of the students and demonstrated how a collegial effort between nurse educators in two universities and long distance collaboration can benefit students who may someday deliver care in rural communities.